The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmed.2022.915152
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Peripheral Resistin and the Severity of Acute Pancreatitis: A Meta-Analysis

Abstract: IntroductionResistin is a small secretory adipokine which is implicated to obesity and associated diseases. Recently, plenty of research papers have been conducted to explore the association between peripheral resistin and the severity of acute pancreatitis (AP). However, the results were controversial. In this study, we aimed to confirm the effect of peripheral resistin and the development of acute pancreatitis.MethodsA comprehensive online search was performed using the PubMed, Embase, Web of Science, CNKI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF . MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis. Accumulating evidence shows that MMP9 [133], S100A12 [148], HP (haptoglobin) [149], OSM (oncostatin M) [150], PRDM5 [151], TSPO (translocator protein) [152], IL18RAP [153], ADAMDEC1 [154], IL1RN [155], SCN9A [156], FADS2 [157], NCF4 [158], SERPINB1 [159], TNFRSF13B [160], IL2RB [161], DLG5 [162], FASLG (Fas ligand) [163], GPR68 [164], IL2RA [161], TCF4 [165], TAGAP (T cell activation RhoGTPase activating protein) [166], ABCB1 [167], FCRL3 [168], ITGB7 [169], PTGER4 [170] and TRAF3IP2 [171] are altered expression in gastrointestinal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF . MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis. Accumulating evidence shows that MMP9 [133], S100A12 [148], HP (haptoglobin) [149], OSM (oncostatin M) [150], PRDM5 [151], TSPO (translocator protein) [152], IL18RAP [153], ADAMDEC1 [154], IL1RN [155], SCN9A [156], FADS2 [157], NCF4 [158], SERPINB1 [159], TNFRSF13B [160], IL2RB [161], DLG5 [162], FASLG (Fas ligand) [163], GPR68 [164], IL2RA [161], TCF4 [165], TAGAP (T cell activation RhoGTPase activating protein) [166], ABCB1 [167], FCRL3 [168], ITGB7 [169], PTGER4 [170] and TRAF3IP2 [171] are altered expression in gastrointestinal complications.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 11 studies involving 892 AP patients found that circulating resistin levels were significantly higher in patients with SAP than those with mild AP, suggesting that elevated resistin levels may predict AP. [77] Activin A, a member of the TGF-β superfamily, has recently emerged as a significant potential mediator of inflammation in AP. Activin A is released into the bloodstream during inflammatory events and modulates inflammatory responses.…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…A meta-analysis of 11 studies involving 892 AP patients found that circulating resistin levels were significantly higher in patients with SAP than those with mild AP, suggesting that elevated resistin levels may predict AP. [77]…”
Section: Pathologic Responses Of the Acinar Cell That Drive Ap And Th...mentioning
confidence: 99%
“…Visfatin promotes the release of pro-inflammatory cytokines IL-1β, IL-6 and TNF-α from peripheral monocytes [17][18][19] Despite many studies having explored the relationship between adipokines and SAP, the findings have been inconsistent. Furthermore, although a meta-analysis of the relationship between adipokines and SAP has recently been published [20], it only statistically examined the relationship between resistin and SAP, failing to address the correlation between other adipokines and SAP.…”
Section: Introductionmentioning
confidence: 99%